The why, what and how of career research: a review and recommendations for future study. Issue 1 (25th January 2022) - Baruch, Yehuda; Sullivan, Sherry E.
Abstract : Purpose: The field of careers studies is complex and fragmented. The aim of this paper is to detail why it is important to study careers, what we study and how we study key issues in this evolving field. Design/methodology/approach: Key theories, concepts and models are briefly reviewed to lay the groundwork for offering an agenda for future research. Findings: The authors recommend ten key directions for future research and offer specific questions for further study. Research limitations/implications: This paper contributes to the development of the theoretical underpinning of career studies. Practical implications: The authors hope that the proposed agenda for future research will help advance the field and encourage more research on understudied, but important, topics. Originality/value: This paper presents a comprehensive view of research on contemporary careers.